Zinc halide perovskite material with high-efficiency blue light emission performance and preparation method and application thereof

Synthesis of 0-dimensional compounds based on free [ZnBr4]2-tetrahedron as the center through hydrothermal reaction method, solving the scarcity of high-efficiency and stable blue luminescent OD metal halides in the prior art, and achieving high-efficiency blue light emission performance halogenation The preparation of zinc perovskite materials has important application prospects for solid-state luminescence and diode display.

CN116410157BActive Publication Date: 2025-01-03JINING UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310240533.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-14
Publication Date
2025-01-03
Estimated Expiration
2043-03-14

AI Technical Summary

Technical Problem

In the prior art, efficient and stable blue luminescent OD metal halides are relatively scarce, limiting the application of lead-free metal perovskites in high-definition displays and lighting equipment.

Method used

The hydrothermal reaction method was used to synthesize the 0-dimensional compound based on free [ZnBr4]2-tetrahedron as the center under medium and low temperature solutions. The reaction of organic amines and zinc halide in hydrohalogenic acid and organic solvents was prepared to produce high-efficiency Zinc halide perovskite material with blue light emission performance.

Benefits of technology

Under ultraviolet excitation, the prepared 0D hybrid zinc halide perovskite material showed bright blue light emission, with a maximum light quantum yield of 17.28%. It is simple to prepare and inexpensive, with important solid-state light emission and diode display application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116410157B_ABST
    Figure CN116410157B_ABST
Patent Text Reader

Abstract

The present invention discloses a zinc halide perovskite material with high-efficiency blue light emission performance and its preparation method and application, belonging to the technical field of solid-state photoluminescent materials. The technical scheme is: prepare a series of free [ZnBr ·4· ] · 2‑ · Tetrahedron-centered 0-dimensional compounds, including [H ·2· NMPz]ZnBr ·4· ·H ·2· O(NMPz=1-methylpiperazine), [H ·2· MPz]ZnBr ·4· (MPz = 2-methylpyrazine) and [H ·2· AMPd]ZnBr ·4· .H ·2· O(AMPd=4-aminomethylpiperidine). Under ultraviolet light excitation, these 0D hybrid zinc halide perovskites show bright blue light emission (444-445nm) from self-trapped excitons, with a maximum photon quantum yield (PLQY) of 17.28%. This material has important application prospects in solid-state light emitting and diode display.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solid-state photoluminescent materials, and in particular to a zinc halide perovskite material with high-efficiency blue light emission performance, a preparation method and application thereof. Background Art

[0002] Halide perovskite materials have excellent and tunable optical and electrical properties and have been widely studied in solar cells, light-emitting diodes (LEDs), and photodetectors. Among them, CsPbX3 perovskites synthesized under medium and low temperature solution conditions have excellent luminescence performance, narrow half-width (FWHM, 12-25nm), wide color gamut (~150% NTSC), continuously tunable band gap, low cost and easy synthesis conditions, etc., and have unique applications in solid-state light-emitting diodes, X-ray scintillation, and remote thermal imaging. In the zero-dimensional (0D) organic-inorganic hybrid lead halide system, the metal halide as anion is isolated and surrounded by organic cations to form a single crystalline compound with a periodic structure. This hybrid formed by halide anions and organic cations with wide band gaps provides a good platform for the metal halide family, thus forming a perfect "host-guest" structure. In this structure, the isolated metal halide polyhedral unit avoids interaction with other polyhedrons, which determines the excellent performance of the 0D perovskite system. Although 0D lead halides have excellent photophysical properties, the toxicity of lead seriously hinders the practical application of this type of luminescent materials. Therefore, the development strategy focuses on preparing efficient lead-free luminescent materials through crystal engineering at the molecular level.

[0003] To date, various lead-free metal ions have been used as optically active centers with different outer shell electron arrangements and coordination configurations, such as Cu + ,Ge 2+ Sn 2+ 、In 3+ , Sb 3+ 、Zn 2+ Surprisingly, it has been found that + , Mn 2+ Sn 3+ , Sb 3+ 、In 3+ Green, yellow, and red luminescence with high PLQY values ​​is achieved in 0D halide single crystals. However, blue emitting 0D metal halides with high efficiency and stability are relatively rare and still challenging. Therefore, it is very important to design environmentally friendly lead-free 0D metal perovskites as efficient blue emitters to achieve balanced development of the three primary colors in high-definition displays and lighting equipment. Summary of the invention

[0004] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art, provide a zinc halide perovskite material with high-efficiency blue light emission performance and its preparation method and application, and prepare a series of free [ZnBr4] 2- Tetrahedron-centered 0D compounds, under ultraviolet light excitation, these 0D hybrid zinc halide perovskites show bright blue light emission (444-445nm) from self-trapped excitons. This material has important application prospects in solid-state light emitting and diode displays.

[0005] The technical solution of the present invention is:

[0006] In a first aspect, a method for preparing a zinc halide perovskite material with high-efficiency blue light emitting performance is disclosed, comprising the following steps:

[0007] 1) dissolving an organic amine and a zinc halide in a mixed solution of a hydrohalic acid and an organic solvent, stirring the mixture until dissolved to obtain a mixed solution, and placing the solution into a reaction vessel;

[0008] 2) The reaction vessel is sealed, and the mixed solution is subjected to a hydrothermal reaction. After the reaction is completed, the mixed solution is naturally cooled to room temperature, and the target compound is obtained after washing, suction filtration and drying;

[0009] In the step 1), the organic amine is 1-methylpiperazine, 2-methylpyrazine or 4-aminomethylpiperidine.

[0010] Preferably, in step 1), the hydrohalic acid is hydrobromic acid, the organic solvent is methanol, and the zinc halide is zinc bromide.

[0011] Preferably, the reaction temperature in step 2) is 80-90° C. and the reaction time is 5-7 days.

[0012] Preferably, the hydrohalic acid is hydrobromic acid, the zinc halide is zinc bromide, the organic solvent is methanol, and when the organic amine is 1-methylpiperazine, the molar ratio of 1-methylpiperazine to zinc bromide is 1:(0.8-1.2); when the organic amine is 2-methylpyrazine, the molar ratio of 2-methylpyrazine to zinc bromide is 1:(0.85-1.25); when the organic amine is 4-aminomethylpiperidine, the molar ratio of 4-aminomethylpiperidine to zinc bromide is 1:(0.9-1.3).

[0013] In a second aspect, a zinc halide perovskite material with high-efficiency blue light emission performance is disclosed.

[0014] Preferably, when the organic amine is 1-methylpiperazine, the structure of the prepared compound 1 is [H2NMPz]ZnBr4·H2O (NMPz = 1-methylpiperazine), the crystal system space group is P21 / c, and the unit cell parameters are α=γ=90°,β=97.496(2),Z=4,the unit cell volume is When the organic amine is 2-methylpyrazine, the structure of the prepared compound 2 is [H2MPz]ZnBr4 (MPz = 2-methylpyrazine), the crystal system space group is P21 / n, and the unit cell parameters are α=γ=90°,β=90.7070(10),Z=4,the unit cell volume is When the organic amine is 4-aminomethylpiperidine, the structure of the prepared compound 3 is [H2AMPd]ZnBr4.H2O (AMPd = 4-aminomethylpiperidine), the crystal system space group is Pc, and the unit cell parameters are α=γ=90°,β=101.66(8),Z=4,the unit cell volume is

[0015] Thirdly, the application of zinc halide perovskite materials with high-efficiency blue light emission performance in the field of solid-state light emitting and diode display is disclosed.

[0016] Compared with the prior art, the present invention has the following beneficial effects:

[0017] The present invention prepares a series of free [ZnBr4] 2- The tetrahedron-centered 0-dimensional compounds [H2NMPz]ZnBr4·H2O, [H2MPz]ZnBr4 and [H2AMPd]ZnBr4·H2O all belong to the blue light emission region. Under ultraviolet light excitation, these 0D hybrid zinc halide perovskites show bright blue light emission (444-445nm) from self-trapped excitons, with a maximum light quantum yield (PLQY) of 17.28%. Moreover, the preparation is simple and the cost is low. This material has important application prospects in solid-state luminescence. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is a crystal structure diagram of compound 1-3 of the present invention.

[0019] Figure 2 It is the powder diffraction structure diagram of compound 1 (a), compound 2 (b) and compound 3 (c) of the present invention.

[0020] Figure 3 It is the solid-state UV-visible optical absorption spectra of compound 1 (a), compound 2 (b) and compound 3 (c) of the present invention.

[0021] Figure 4 The excitation spectra (left peak in the figure) and emission spectra (right peak in the figure) of Compound 1(a), Compound 2(b) and Compound 3(c) of the present invention at room temperature are shown.

[0022] Figure 5 It is the International Commission on Illumination (CIE) 1931 color coordinate diagram of the present invention, and a schematic diagram of the light-emitting positions of compound 1, compound 2, and compound 3.

[0023] Figure 6 PLQE emission spectra of Compound 1 (a), Compound 2 (b) and Compound 3 (c) of the present invention.

[0024] Figure 7 It is a comparison chart of the PLQE of compounds 1-3 of the present invention and Cs2ZnBr4 in Example 4.

[0025] Figure 8 It is the photoluminescence decay graph and fitting curve graph of compounds 1-3 of the present invention at room temperature. DETAILED DESCRIPTION

[0026] In order to enable those skilled in the art to better understand the technical solutions in the present invention, the technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the accompanying drawings in the embodiments of the present invention. The experimental methods described in the following embodiments are conventional methods unless otherwise specified; if no specific techniques or conditions are specified in the embodiments, they are carried out according to the techniques or conditions described in the literature in the field or according to the product instructions; the reagents and materials, unless otherwise specified, can be obtained from commercial channels.

[0027] 1. Raw materials used

[0028] The raw materials used in the examples were all provided by Aladdin Reagent Company: ZnBr2 (purity 99.5%), 1-methylpiperazine (purity 98%), 2-methylpyrazine (purity 98%), 4-aminomethylpiperidine (purity 98%), methanol (purity 99%), ethanol (purity 99%), and HBr aqueous solution (purity 37%).

[0029] 2. Instruments and test methods

[0030] The electric heating blast drying oven was provided by Shanghai Yiheng Scientific Instrument Co., Ltd., model DHG-9240(A).

[0031] The hydrothermal kettle for the hydrothermal reaction was produced by Jinan Henghua Technology Co., Ltd. and had a capacity of 15 mL.

[0032] The crystal structure was determined by single crystal X-ray diffractometer (SMART APEXII, Bruker, Germany).

[0033] The crystals were ground into powder and the diffraction data were collected using an X-ray powder diffractometer (Bruker D8 ADVANCE).

[0034] The absorption peak of the powder sample was measured using a UV-visible spectrophotometer (PE Lambda 900).

[0035] The photoluminescence (PL) spectrum test, photoluminescence quantum efficiency (PLQE) test and time-resolved decay data test were performed using a fluorescence spectrometer (FLS920 from Edinburgh Company), and the average lifetime was obtained by exponential function fitting.

[0036] The photoluminescence chromaticity coordinates of the samples were calculated using the International Commission on Illumination (CIE) color coordinate calculation software based on the emission spectrum.

[0037] Example 1 Preparation of [H2NMPz]ZnBr4·H2O (Compound 1)

[0038] 1) Add 1 mmol ZnBr2 and 1 mmol 1-methylpiperazine (NMPz) to a mixed solution of 1 mL hydrobromic acid and 3 mL methanol, stir until dissolved, and then put the mixed solution into a 15 mL glass bottle and seal it.

[0039] 2) The sealed glass bottle was placed in an electric hot air drying oven with programmable temperature control, and the reaction was carried out at a constant temperature of 80° C. for 5 days; after the reaction was completed, it was cooled to room temperature, the glass bottle cover was opened, and the reaction solution was poured into a 50 mL small beaker for washing and suction filtration. The obtained solid was air-dried to obtain a colorless flaky crystalline material, which was washed with ethanol and dried naturally to obtain the target product [H2NMPz]ZnBr4·H2O (compound 1) with a yield of 68%.

[0040] Example 2 Preparation of [H2MPz]ZnBr4 (Compound 2)

[0041] 1) Add 1 mmol ZnBr2 and 1.2 mmol 2-methylpyrazine (MPz) to a mixed solution of 1 mL hydrobromic acid and 3 mL methanol, stir for 20 minutes, and then put the mixed solution into a 15 mL glass bottle and seal it.

[0042] 2) The sealed glass bottle was placed in an electric blast drying oven with programmable temperature control, and the reaction was carried out at a constant temperature of 90°C for 7 days. After the reaction was completed, it was cooled to room temperature, the glass bottle cover was opened, and the reaction solution was poured into a 50 mL small beaker for washing and suction filtration. The obtained solid was dried to obtain a colorless block crystalline material, namely [H2MPz]ZnBr4 (Compound 2), and the yield was 65%.

[0043] Example 3 Preparation of [H2AMPd]ZnBr4.H2O (Compound 3)

[0044] 1) Add 1 mmol ZnBr2 and 0.85 mmol 4-aminomethylpiperidine (AMPd) to a mixed solution of 1 mL hydrobromic acid and 4 mL methanol, stir for 20 minutes, and then put the mixed solution into a 15 mL glass bottle and seal it.

[0045] 2) The sealed glass bottle was placed in an electric blast drying oven with programmable temperature control, and the reaction was maintained at a constant temperature of 80°C for 5 days. After the reaction was completed, the mixture was cooled to room temperature, and the mixture was poured into a 50 mL small beaker for washing and filtration. The obtained solid was dried to obtain a colorless block crystalline material, namely [H2AMPd]ZnBr4·H2O (compound 3), with a yield of 70%.

[0046] Figure 1 The crystal structure diagram of compound 1-3. Compounds [H2NMPz]ZnBr4·H2O, [H2MPz]ZnBr4, and [H2AMPd]ZnBr4·H2O all belong to the monoclinic system. The molecular formula of the finally prepared compound 1 is [H2NMPz]ZnBr4·H2O(C5H 16 ON2ZnBr4), belongs to the monoclinic system, P21 / c space group, and the unit cell parameters are α=γ=90°,β=97.496(2),Z=4,the unit cell volume is The molecular formula of compound 2 is [H2MPz]ZnBr4(C5H 14 N2ZnBr4) belongs to the monoclinic system, P21 / n space group, and the unit cell parameters are α=γ=90°,β=90.7070(10),Z=4,the unit cell volume is The molecular formula of compound 3 is [H2AMPd]ZnBr4·H2O(C6H 16 ON2ZnBr4) belongs to the monoclinic system, Pc space group, and the unit cell parameters are α=γ=90°,β=101.66(8),Z=4,the unit cell volume is

[0047] Figure 2 The powder diffraction structure diagram of compound 1-3. It can be seen from the figure that the polycrystalline powder diffraction patterns of [H2NMPz]ZnBr4·H2O, [H2MPz]ZnBr4, and [H2AMPd]ZnBr4·H2O are consistent with the theoretical data of single crystal structure simulation, indicating that the purity of the polycrystalline powder is high and close to the theoretical value.

[0048] like Figure 3As shown, solid-state UV-visible optical absorption spectra of the ground powder samples of the compounds [H2NMPz]ZnBr4·H2O, [H2MPz]ZnBr4, and [H2AMPd]ZnBr4·H2O were tested. The three materials showed obvious absorption peaks at around 250, 255, and 256 nm, respectively, and the optical band gaps were 4.96 eV, 4.86 eV, and 4.84 eV, respectively, corresponding to colorless crystals.

[0049] In order to verify the application of these perovskite materials in the field of solid-state light emitting and diode display, their photoluminescence properties are studied, such as Figure 4 As shown, the compounds [H2NMPz]ZnBr4·H2O, [H2MPz]ZnBr4, and [H2AMPd]ZnBr4·H2O all produced a high-frequency emission peak under the excitation of 375, 368, and 363 nm ultraviolet light, respectively, with peak values ​​of 444, 445, and 444 nm, half-peak widths of 73, 86, and 92 nm, and smaller Stokes shifts of 69, 77, and 81 nm; the corresponding International Commission on Illumination (CIE) chromaticity coordinates (x, y) are (0.20, 0.16), (0.19, 0.13), and (0.18, 0.15), all of which belong to the blue light emission region ( Figure 5 ).

[0050] like Figure 6 As shown, the photoluminescence quantum efficiency performance of compounds 1-3 was studied, and the calculation was based on the equation: QE =I S / (E R -E S ), where I S represents the fluorescence emission spectrum of the sample, E R is the spectrum of the excitation light of the empty integrating sphere (without sample), E S is the excitation spectrum of the excited sample. The PLQE of the compound [H2NMPz]ZnBr4·H2O, [H2MPz]ZnBr4, [H2AMPd]ZnBr4·H2O crystals were measured to be approximately 15.78, 16.25 and 17.28%.

[0051] like Figure 8As shown, the fluorescence properties of compounds 1-3 were studied. The time-resolved emission spectra of compounds [H2NMPz]ZnBr4·H2O, [H2MPz]ZnBr4, and [H2AMPd]ZnBr4·H2O were monitored at 444, 445, and 444 nm, respectively, and were fitted using a single exponential function I(t)=I0exp(-t / τ), where I(t) represents the luminescence intensity, I0 is the fluorescence intensity at time 0, t is the time after excitation, and τ refers to the luminescence lifetime. The average lifetimes of the three compounds are 4.557, 4.633, and 6.899 μs, respectively. The longer emission peak lifetimes indicate that the compounds have fluorescent properties.

[0052] Comparative Example 1

[0053] This comparative example provides a zinc halide perovskite material Cs2ZnBr4, see Angew.Chem., Int.Ed.2020,59,21414 for details.

[0054] The comparison of PLQE of compounds 1-3 of the present invention and Cs2ZnBr4 in Example 4 is shown in FIG. Figure 7 The PLQE of the compound 1-3 crystals measured in the present application is about 15.78, 16.25 and 17.28%, which is much higher than the PLQE of the inorganic material Cs2ZnBr4 in Comparative Example 1, which is 3.6%.

[0055] Although the present invention has been described in detail by referring to the accompanying drawings and in combination with the preferred embodiments, the present invention is not limited thereto. Without departing from the spirit and essence of the present invention, a person of ordinary skill in the art may make various equivalent modifications or substitutions to the embodiments of the present invention, and these modifications or substitutions shall be within the scope of the present invention. Therefore, the protection scope of the present invention shall be subject to the protection scope of the claims.

Claims

1. A method for preparing a zinc halide perovskite material with high-efficiency blue light emitting performance, comprising the following steps: 1) dissolving the organic amine and zinc halide in a mixed solution of hydrohalic acid and an organic solvent, stirring thoroughly until dissolved to obtain a mixed solution, and placing the solution into a reaction vessel; 2) The reaction vessel is sealed, and the mixed solution is subjected to a hydrothermal reaction. After the reaction is completed, the mixed solution is naturally cooled to room temperature, and the target compound is obtained after washing, filtration and drying; In the step 1), the organic amine is 2-methylpyrazine or 4-aminomethylpiperidine; When the organic amine is 2-methylpyrazine, the structure of the prepared compound 2 is [H2MPz]ZnBr4 (MPz=2-methylpyrazine), and the crystal system space group is P twenty one / n, The unit cell parameters are a =8.69730(10)Å, b =15.3095(2)Å, c =10.1270(10)Å, α = γ =90º, β =90.7070(10), Z =4, the unit cell volume is V =1348.32(3)Å 3 When the organic amine is 4-aminomethylpiperidine, the structure of the prepared compound 3 is [H2AMPd]ZnBr4.H2O (AMPd = 4-aminomethylpiperidine), and the crystal space group is Pc, The unit cell parameters are a =6.5192(10)Å, b =7.6210(10)Å, c =15.2595(2)Å, α = γ =90º, β =101.66(8), Z =4, the unit cell volume is V =742.490(18)Å 3 .

2. The method for preparing the zinc halide perovskite material with high-efficiency blue light emission performance according to claim 1, characterized in that: In step 1), the hydrohalic acid is hydrobromic acid, the organic solvent is methanol, and the zinc halide is zinc bromide.

3. The method for preparing the zinc halide perovskite material with high-efficiency blue light emitting performance according to claim 1, characterized in that: The reaction temperature in step 2) is 80-90°C and the reaction time is 5-7 days.

4. The method for preparing the zinc halide perovskite material with high-efficiency blue light emitting performance according to claim 1, characterized in that: The hydrohalic acid is hydrobromic acid, the zinc halide is zinc bromide, and the organic solvent is methanol; when the organic amine is 2-methylpyrazine, the molar ratio of 2-methylpyrazine to zinc bromide is 1:(0.85-1.25); when the organic amine is 4-aminomethylpiperidine, the molar ratio of 4-aminomethylpiperidine to zinc bromide is 1:(0.9-1.3).

5. Application of the zinc halide perovskite material with high-efficiency blue light emission performance prepared by the preparation method according to claim 1 in the field of solid-state light emitting and diode display.